Manufacturing method of loudspeaker diaphragm, loudspeaker diaphragm and loudspeaker

By subjecting the speaker diaphragm to molding, cathode arc deposition, and thermal evaporation treatments, combined with a high-modulus carbon fiber skeleton and high-rigidity glue bonding, the diaphragm's stability problem under high-frequency vibration is solved, achieving stable vibration and improved sound quality in the high-frequency band.

CN120711345AActive Publication Date: 2025-09-26RAYLEIGH LABS TECH (SHENZHEN) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511160318.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-09-26
Estimated Expiration
2045-08-19

AI Technical Summary

Technical Problem

Existing speaker diaphragms are not stable enough under high-frequency vibrations, and are prone to nonlinear vibrations or local resonances, resulting in distorted sound quality.

Method used

The diaphragm matrix with a folded edge structure is formed by high molecular polymer molding, and diamond coating is formed by cathode arc deposition technology. Combined with thermal evaporation deposition processing, high modulus carbon fiber prepreg is used to make the carbon fiber voice coil frame, and it is bonded with high-rigidity glue. Finally, a frequency sweep test is performed to adjust the vibration characteristics.

Benefits of technology

The rigidity and vibration resistance of the diaphragm are improved, ensuring the vibration consistency and vibration resistance in a wide frequency band, especially in the high frequency band, improving the sound clarity and frequency response, and extending the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120711345A_ABST
    Figure CN120711345A_ABST
Patent Text Reader

Abstract

The invention discloses a loudspeaker diaphragm manufacturing method, a loudspeaker diaphragm and a loudspeaker, and the manufacturing method comprises the steps: carrying out the mold pressing of a high-molecular polymer, forming an edge-folded structure diaphragm substrate, placing the edge-folded structure diaphragm substrate in a deposition cavity, carrying out the cathodic arc deposition, and carrying out the thermal evaporation deposition, and obtaining an evaporation diaphragm; selecting a high-modulus carbon fiber prepreg, and carrying out wet winding forming treatment on a first mold at a preset angle to obtain a carbon fiber voice coil skeleton; bonding the evaporation diaphragm and the carbon fiber voice coil skeleton through high-rigidity glue to obtain a diaphragm assembly; and performing a frequency sweep test on the diaphragm assembly, and adjusting the vibration characteristic of the diaphragm assembly according to a test result until a preset performance requirement is met, thereby obtaining the loudspeaker diaphragm assembly. The performance and the stability of the diaphragm assembly are remarkably improved through a multi-step collaborative process, and the defects that in the prior art, the diaphragm is insufficient in high-frequency vibration stability, poor in coating uniformity, complex in process and the like are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of loudspeakers, and in particular to a method for manufacturing a loudspeaker diaphragm, ... and a loudspeaker. Background Art

[0002] The speaker diaphragm is the component that determines the sound quality of a speaker system. Its manufacturing method directly affects sound clarity, frequency response, and dynamic range. In existing technology, speaker diaphragms are typically manufactured from polymers, metals, or composite materials. The diaphragm base is formed through processes such as molding, injection molding, or hot pressing. The diaphragm assembly is then completed through coating or bonding to the voice coil bobbin. These methods are somewhat effective in achieving basic sound quality requirements, such as providing the necessary vibration response and structural stability.

[0003] However, existing diaphragm manufacturing processes often suffer from a core technical issue: insufficient stability at high frequencies. At high frequencies or high power output, the diaphragm is prone to nonlinear vibrations or local resonances, resulting in distorted sound quality. This makes clear and stable sound difficult to achieve, especially in the high-frequency range.

[0004] To improve the performance of the diaphragm under high-frequency vibration, existing technologies enhance the vibration resistance of the diaphragm by introducing high-rigidity materials or optimizing the surface treatment process. For example, some technologies apply metal coatings or ceramic coatings on a high-molecular polymer matrix to enhance the rigidity and durability of the diaphragm; or use carbon fiber composite materials to make the diaphragm or voice coil frame to increase the modulus of the overall structure. However, although metal coatings can improve rigidity, the uniformity of the coating process is difficult to control, which can easily lead to uneven stress distribution on the diaphragm surface, thereby causing local deformation during high-frequency vibration. The wet molding or bonding process of carbon fiber materials is complex and requires high equipment precision. If not properly controlled, tiny defects may appear at the junction of the diaphragm and the voice coil frame, further exacerbating the instability of high-frequency vibration. In addition, existing coating technologies may peel off or suffer fatigue damage during long-term use, reducing the reliability and service life of the diaphragm. Summary of the Invention

[0005] The purpose of this application is to provide a method for manufacturing a loudspeaker diaphragm to solve the technical problem in the prior art that the diaphragm has insufficient stability under high-frequency vibration.

[0006] To achieve this goal, this application adopts the following technical solutions: A method for manufacturing a loudspeaker diaphragm, comprising: Molding a high molecular polymer to form a folded edge structure diaphragm substrate, placing the folded edge structure diaphragm substrate in a deposition chamber for cathode arc deposition to obtain a diamond-coated diaphragm; In a vacuum environment, the diamond-coated diaphragm is placed in a thermal evaporation chamber, and a thermal evaporation deposition process is performed on the diamond-coated diaphragm to obtain a vapor-deposited diaphragm; High modulus carbon fiber prepreg is selected and wet-wound at a preset angle on the first mold to obtain a carbon fiber voice coil bobbin; Bonding the evaporated diaphragm and the carbon fiber voice coil frame with high-rigidity glue to obtain a diaphragm assembly; A frequency sweep test is performed on the diaphragm assembly, and the vibration characteristics of the diaphragm assembly are adjusted according to the test results until the preset performance requirements are met, thereby obtaining a loudspeaker diaphragm assembly.

[0007] Furthermore, the high molecular polymer is a mixture of any one or more of polyimide, polyetheretherketone, polyethylene terephthalate, and polycarbonate.

[0008] Furthermore, the step of molding the high molecular polymer to form the diaphragm matrix with a hem-folded structure includes: Under the conditions of a second mold temperature of 250-300° C. and a pressure of 10-15 MPa, the polymer is molded to obtain an initial hem-folded matrix, wherein the second mold adopts an asymmetric wavy design, the amplitude of the wavy design of the second mold is 0.2-0.5 mm, and the wave pitch is 1.0-1.5 mm; The initial folded edge substrate is placed in an ultrasonic cleaning device for cleaning, using deionized water as the cleaning medium, setting the ultrasonic frequency to 40-60 kHz, and the cleaning time to 5-10 minutes to obtain an initial diaphragm substrate; performing vacuum drying on the initial diaphragm matrix to obtain a dry diaphragm matrix; The folded edge structure of the dry diaphragm substrate is corrected by laser to obtain a folded edge structure diaphragm substrate, wherein the laser wavelength is 532 nm and the pulse width is 10-20 ns.

[0009] Furthermore, the step of placing the folded edge structure diaphragm substrate in a deposition chamber for cathode arc deposition to obtain a diamond-coated diaphragm includes: The folded edge structure diaphragm substrate is placed in a deposition chamber, the deposition chamber is evacuated to 10-5 Pa, hydrogen is introduced as a protective gas, and the deposition chamber is preheated to 80-100° C. Using a high-purity graphite target as a cathode, starting cathode arc discharge to perform low-speed pre-deposition on the surface of the folded edge structure diaphragm substrate, wherein the DC voltage of the cathode arc discharge is 400 V, the arc current is 40 A, the deposition rate is 0.2-0.3 nm / s, and the deposition time is 5-10 minutes; The main deposition treatment is performed on the surface of the folded edge structure diaphragm substrate, the arc current is adjusted to 50~80A, and a -100V pulse bias is applied, the deposition rate is increased to 0.5~1nm / s, and the deposition is continued for 20~30 minutes. At the same time, hydrogen is introduced into the deposition chamber to obtain a diamond-coated diaphragm.

[0010] Furthermore, the step of placing the diamond-coated diaphragm in a thermal evaporation chamber under a vacuum environment and performing thermal evaporation deposition on the diamond-coated diaphragm to obtain the evaporated diaphragm includes: The diamond-coated diaphragm is placed in a thermal evaporation chamber, the vacuum degree in the thermal evaporation chamber is adjusted to 10-7 Pa, argon is introduced as a protective gas, and the temperature in the thermal evaporation chamber is raised to 200-220°C and kept constant; Using a platinum target as an evaporation source, heating the platinum target to 1800° C. using an electron beam heating device, controlling the deposition rate to 0.2 nm / s, and performing thermal evaporation deposition on the surface of the diamond-coated diaphragm for 15 to 20 minutes to obtain a primary platinum-coated diaphragm; A titanium target was used as an auxiliary evaporation source, and the titanium target was heated to 1600°C by an electron beam heating device. The deposition rate was controlled to be 0.1 nm / s, and a secondary thermal evaporation deposition treatment was performed on the surface of the primary platinum-coated diaphragm. The deposition time was 10 minutes to obtain the evaporated diaphragm.

[0011] Furthermore, the step of selecting a high modulus carbon fiber prepreg and performing a wet winding molding process on a first mold at a preset angle to obtain a carbon fiber voice coil bobbin includes: Performing a wet winding process on the first mold with the high modulus carbon fiber prepreg at a preset angle, wherein the preset angle is 40-50 degrees and the number of winding layers is 3-6, to obtain a primary winding body; The primary winding body and the first mold are placed in a high-temperature curing furnace for curing treatment, maintained at a temperature of 120-125° C. for 120-150 minutes, and then raised to 180-190° C. and maintained for 200-230 minutes to obtain a cured carbon fiber skeleton; The solidified carbon fiber skeleton is placed in a deposition chamber, and a nano-scale silicon carbide coating is deposited on the surface of the solidified carbon fiber skeleton, wherein the target power is 200-300W and the deposition time is 10-15 minutes to obtain the carbon fiber voice coil skeleton.

[0012] Furthermore, the step of bonding the evaporated diaphragm and the carbon fiber voice coil frame with high-rigidity glue to obtain a diaphragm assembly includes: Placing the evaporated diaphragm and the carbon fiber voice coil frame in an ultraviolet ozone cleaning device to clean the surfaces of the evaporated diaphragm and the carbon fiber voice coil frame; The epoxy resin and the curing agent are mixed and stirred in a mass ratio of 10 to 9:1, and silica particles are added during the mixing process to obtain a high-rigidity glue; Applying the high-rigidity glue in a dispensing amount of 0.015-0.025 g to the bonding area of ​​the cleaned evaporated diaphragm and the carbon fiber voice coil frame, and then performing an alignment bonding process to obtain a preliminary bonding assembly; The preliminary bonding assembly is placed in a constant temperature curing oven and subjected to low temperature curing treatment at a temperature of 25 to 30°C for 1.5 to 2.5 hours to obtain the diaphragm assembly.

[0013] Furthermore, the step of performing a frequency sweep test on the diaphragm assembly and adjusting the vibration characteristics of the diaphragm assembly according to the test results until the preset performance requirements are met to obtain the loudspeaker diaphragm assembly includes: Applying a sinusoidal wave excitation signal to the diaphragm assembly within a preset frequency range, measuring the amplitude, phase, and frequency response characteristics of the diaphragm assembly, and obtaining preliminary vibration characteristic data; Determining whether the preliminary vibration characteristic data meets preset performance requirements; If not, based on the difference between the preliminary vibration characteristic data and the preset performance requirements, a polymer damping material is coated on the edge area of ​​the diaphragm assembly to adjust the boundary vibration characteristics of the diaphragm assembly until the preliminary vibration characteristic data meets the preset performance requirements, thereby obtaining a speaker diaphragm assembly.

[0014] The present application also discloses a loudspeaker diaphragm, which is manufactured using any of the above-mentioned methods for manufacturing a loudspeaker diaphragm.

[0015] The present application also discloses a loudspeaker, comprising the above-mentioned loudspeaker diaphragm, and a magnetic circuit system and a voice coil assembly connected to the loudspeaker diaphragm.

[0016] Compared with the prior art, this application has the following beneficial effects: The manufacturing method of the loudspeaker diaphragm of the present application forms a folded-edge structure diaphragm substrate by molding a high molecular polymer, and forms a diamond-coated diaphragm on the substrate using cathode arc deposition technology, and effectively enhances the rigidity of the diaphragm by utilizing the high hardness of the diamond material, thereby reducing nonlinear deformation and local resonance during high-frequency vibration; further optimizes the diaphragm surface through thermal evaporation deposition in a vacuum environment to obtain a vapor-deposited diaphragm, thereby improving the diaphragm's stress resistance; selects high modulus carbon fiber prepreg and wet-winds the carbon fiber voice coil skeleton at a preset angle, thereby enhancing the vibration consistency and vibration resistance of the entire diaphragm assembly in a wide frequency band, especially in the high frequency band; conducts frequency sweep testing and accurately adjusts the vibration characteristics of the diaphragm assembly according to the test results until the preset performance requirements are met, thereby ensuring the final loudspeaker diaphragm assembly's performance in sound clarity, frequency response, and dynamic range. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0018] The structures, proportions, sizes, etc. depicted in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not intended to limit the conditions under which this application can be implemented, and therefore have no substantive technical significance. Any structural modifications, changes in proportional relationships, or adjustments in size should still fall within the scope of the technical contents disclosed in this application without affecting the efficacy and objectives that can be achieved by this application.

[0019] Figure 1 Schematic diagram of the overall steps of the manufacturing method of the loudspeaker diaphragm. DETAILED DESCRIPTION

[0020] In order to make the purpose, features, and advantages of the invention of this application more obvious and easy to understand, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the embodiments described below are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0021] In the description of this application, it should be understood that the terms "upper", "lower", "top", "bottom", "inner", "outer", etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings and are intended only to facilitate the description of this application and simplify the description. They do not indicate or imply that the devices or elements referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore should not be understood as limiting this application. It should be noted that when a component is considered to be "connected" to another component, it may be directly connected to the other component or there may be a centrally located component.

[0022] The technical solution of the present application will be further explained below with reference to the accompanying drawings and through specific implementation methods.

[0023] refer to Figure 1 The present application provides a method for manufacturing a loudspeaker diaphragm, comprising: S1: Molding a high molecular polymer to form a folded edge structure diaphragm substrate, placing the folded edge structure diaphragm substrate in a deposition chamber for cathode arc deposition to obtain a diamond-coated diaphragm; In step S1, polyimide is selected as the polymer, which provides sufficient initial rigidity for the diaphragm and exhibits good processing adaptability. The molecular structure of polyimide ensures its stability under high temperature and pressure. The polyimide is then molded into a diaphragm substrate with a specific geometric structure. The hem design utilizes an asymmetric, wavy structure with an amplitude controlled between 0.2 and 0.5 mm and a pitch between 1.0 and 1.5 mm. The amplitude and pitch parameters of the asymmetric wavy structure effectively disperse vibration stress, enhancing the overall rigidity of the diaphragm while optimizing the vibration mode for smoother sound output. The mold temperature must be controlled between 250 and 300°C. This temperature range allows the polyimide to reach an appropriate softening state for easy shaping while preventing overheating and degradation. The pressure is controlled between 10 and 15 MPa to ensure that the material fully fills the mold and forms a smooth surface. The surface flatness is required to be less than 0.1 μm. The resulting diaphragm substrate has an initial Young's modulus of approximately 100 GPa. The diaphragm substrate needs to be surface treated after molding, and ultrasonic cleaning is used to remove impurities on the substrate surface, such as oil, particles or processing residues. Ultrasonic cleaning is carried out in deionized water with an appropriate amount of detergent, and the cleaning time is about 10 to 15 minutes to ensure a clean surface. After cleaning, the diaphragm substrate is placed in a vacuum drying oven and dried at 120°C for 2 hours to remove moisture and volatile substances, and avoid bubbles or defects caused by volatiles during the vacuum deposition process. The dried substrate is stored in an inert gas (such as nitrogen) environment to prevent oxidation or moisture absorption, thereby maintaining the stability of the surface state. The diaphragm substrate is placed in a vacuum cathode arc deposition chamber, and a layer of high hardness and high rigidity nano-diamond coating is formed on the surface of the diaphragm substrate by cathode arc deposition technology to significantly improve the acoustic performance of the diaphragm. The vacuum degree of the deposition cavity needs to reach 10~ 5 Pa, to avoid interference of air molecules on plasma. High-purity graphite (purity 99.99%) is used as the cathode target material, and by applying a 500V DC voltage and controlling the arc current at 50-80A, a high-density carbon plasma is generated. These carbon plasmas are deposited on the surface of the diaphragm substrate under the action of the electric field to form a nano-diamond coating. During the deposition process, the substrate temperature is maintained at 100-150°C to avoid damage to the polyimide substrate due to overheating, while ensuring the effective deposition of carbon atoms. The deposition rate is controlled at 0.5-1nm / s to form a coating layer with a thickness of 500-800nm. In order to further improve the coating quality, pulse bias technology is used in the deposition process. The bias is set to -100V and the frequency is 20kHz, which can enhance the sp 3 The ratio of bonds makes the Young's modulus of the coating reach 1050GPa, which is close to the hardness of natural diamond, thereby greatly improving the rigidity and high-frequency response of the diaphragm. A trace amount of hydrogen (flow rate 5sccm) is introduced into the deposition chamber to optimize the crystal structure of the coating and reduce internal stress. The introduction of hydrogen can effectively reduce sp2 bond formation, promoting sp 3 The formation of bonds makes the coating have higher hardness and lower surface roughness. Finally, the bonding strength between the obtained nano-diamond coating and the substrate reaches 50N / cm 2 , surface roughness Ra is less than 2nm.

[0024] S2: placing the diamond-coated diaphragm in a thermal evaporation chamber under a vacuum environment, and performing thermal evaporation deposition on the diamond-coated diaphragm to obtain a vapor-deposited diaphragm; In step S2, the diamond-coated diaphragm is placed as a substrate in a high vacuum thermal evaporation chamber, and the vacuum degree of the chamber can be 10 -6 In the specific operation, high-purity platinum (Pt, 99.95% purity) is used as the evaporation source material. Platinum forms a thin film with both damping and conductive properties on the diaphragm surface. During the evaporation process, the platinum material is placed in a crucible within a thermal evaporation chamber and heated to 1800-2000°C using electron beam heating, transforming the platinum from a solid state to a gaseous state. Electron beam heating offers precise temperature control, rapidly heating the platinum above its melting point while preventing contamination of the evaporation source by the crucible material. This results in a platinum film with a thickness of 50-100nm. During the deposition process, the diaphragm substrate rotates at a constant speed of 10 rpm, ensuring uniform deposition of the evaporated platinum atoms on the diaphragm surface and avoiding performance variations caused by uneven film thickness. A trace amount of argon gas, controlled at a flow rate of 2 sccm (standard milliliters per minute), regulates the chamber pressure to prevent oxidation of the platinum material at high temperatures and maintain stability during the evaporation process. The platinum layer acts as a damping layer, effectively suppressing the resonance peak of the diaphragm in the high-frequency range of 60-70kHz. High-frequency resonance peaks are undesirable vibrations generated by the speaker diaphragm at specific frequencies, which may cause distortion or harshness in the sound quality. The addition of the platinum layer quickly attenuates these unwanted vibrations by increasing the damping properties of the diaphragm, making the sound quality softer and more natural. The platinum layer has excellent conductivity, with a surface resistivity controlled at 10 -8 The Ω·m level helps to stabilize the response of the diaphragm under electromagnetic drive and reduce the impact of static electricity accumulation on the diaphragm performance.

[0025] S3: Select high modulus carbon fiber prepreg and perform wet winding molding on the first mold at a preset angle to obtain a carbon fiber voice coil bobbin; In step S3, carbon fiber prepreg is a material formed by pre-impregnating carbon fiber yarn with a resin matrix. High-modulus carbon fiber has an elastic modulus above 300 GPa. Wet winding involves directly winding the prepreg, while still impregnated with resin, onto a mold. The winding process is performed on a cylindrical mold with a diameter of 5-10 mm. The winding angle is set at 45°. This ensures a balance between axial and circumferential mechanical properties, ensuring the tensile strength of the voice coil bobbin and enhancing its torsional resistance. The number of winding layers is 3-5, with a thickness of 0.1-0.15 mm. After winding, the mold is cured in a curing oven at 180°C for 4 hours. This curing process cross-links the resin in the prepreg, forming a strong composite structure. The curing temperature of 180°C is suitable for most epoxy resin systems and allows for the curing reaction to complete without excessive energy consumption. Residual resin on the surface is removed using a 100W plasma cleaner for 5 minutes. Plasma cleaning uses high-energy plasma to bombard the material surface, which can effectively remove organic pollutants and trace resins, while improving surface roughness and enhancing bonding properties.

[0026] S4: bonding the evaporated diaphragm and the carbon fiber voice coil frame with high-rigidity glue to obtain a diaphragm assembly; In step S4, in a dust-free environment, glue with a hardness of 80D and a shear strength of 30 MPa is selected. This glue is a high-performance epoxy or acrylic adhesive with high hardness and excellent mechanical strength, ensuring a stable connection between the diaphragm and voice coil former under high-frequency vibrations. The high hardness (80D) indicates that the glue has high rigidity after curing, effectively transmitting the vibration energy of the diaphragm to the voice coil former. The shear strength of 30 MPa ensures the shear resistance of the bonding interface, preventing delamination during long-term use. Before bonding, the Pt-deposited diaphragm and carbon fiber voice coil former are cleaned with UV-ozone for 10 minutes to increase the surface energy to 50 mN / m. UV-ozone cleaning is a surface modification technology that uses UV light to excite ozone molecules to produce highly reactive oxygen atoms, removing organic contaminants from the surface and increasing surface active sites, thereby improving surface wettability and adhesion. A surface energy of 50 mN / m indicates that the material surface has achieved high polarity, making it suitable for forming a strong chemical and physical bond with the high-rigidity glue. Applying a pressure of 0.5 MPa during bonding ensures a tight fit between the diaphragm and voice coil bobbin, promoting adequate wetting and penetration of the glue at the interface while expelling any small bubbles. The bonded assembly is then cured for two hours at 25°C and 40% humidity. This temperature and humidity ensure a smooth cross-linking reaction while avoiding excessively high humidity, which can lead to moisture absorption, or incomplete curing, which can result from excessively low humidity. The cured diaphragm assembly undergoes a bond strength test, such as measuring the interfacial peel force using a tensile testing machine, to ensure it meets the 40 N / cm² requirement.

[0027] S5: performing a frequency sweep test on the diaphragm assembly, and adjusting the vibration characteristics of the diaphragm assembly according to the test results until the preset performance requirements are met, thereby obtaining a loudspeaker diaphragm assembly; In step S5, after completing steps S1 through S4, the diaphragm assembly, consisting of a diamond-coated diaphragm, a carbon fiber voice coil former, and high-rigidity adhesive, has demonstrated initial structural integrity and acoustic performance potential. A frequency sweep test is then performed to assess whether its vibration characteristics meet design requirements. This frequency sweep test is conducted in a laboratory environment, with the diaphragm assembly mounted on a loudspeaker frame to simulate its operation in an actual loudspeaker system. The test equipment generates a series of continuously varying sinusoidal signals, covering a low- to high-frequency range, such as 20 Hz to 20 kHz, encompassing the perceptible audio frequency range for the human ear. These sinusoidal excitations cause the diaphragm assembly to vibrate accordingly, and the test equipment records parameters such as amplitude, phase, and frequency response, generating a frequency response curve for the diaphragm assembly. This curve provides a visual representation of the diaphragm assembly's vibration behavior at different frequencies, including key characteristics such as the presence of resonance peaks and the flatness of the frequency response. For example, suppose testing reveals a significant resonance peak at 500 Hz, resulting in excessively strong sound output at this frequency. This could potentially cause distortion and require further adjustment. Based on the results of the frequency sweep test, the vibration characteristics of the diaphragm assembly are adjusted. These vibration characteristics primarily include the diaphragm's stiffness, damping, mass distribution, and coupling with the voice coil former. These factors directly impact the speaker's acoustic performance, such as sound clarity, low-frequency immersion, and high-frequency detail. This adjustment process typically involves fine-tuning, which involves making subtle modifications to the diaphragm assembly's structural parameters or material properties. Structural parameter adjustments can include altering the diaphragm's thickness, the geometry of the folded edge structure, or the distribution of bonding points. For example, if testing reveals that the diaphragm's mid-frequency response is not smooth enough, the folded edge structure can be increased or the thickness of the diaphragm edge reduced to optimize its vibration mode. Adjusting the material properties may involve fine-tuning the adhesive's hardness or damping properties, such as using a different adhesive formula to change the coupling stiffness between the diaphragm and voice coil former. If the winding angle or fiber density of the carbon fiber voice coil former significantly affects the vibration characteristics, the prepreg winding parameters can be readjusted and the former remade. After adjustments, the diaphragm assembly is subjected to another frequency sweep test to generate a new frequency response curve and compare it with the preset acoustic performance requirements. This process requires multiple iterations until the diaphragm assembly's vibration characteristics meet the desired targets, such as a flat frequency response curve within the target frequency band with no noticeable resonance peaks or attenuation.

[0028] In one embodiment scenario, the diaphragm assembly is required to meet the following preset performance requirements: a frequency response curve deviation of no more than ±3dB within the range of 20Hz to 20kHz, with no significant resonance peaks. In step S5, the diaphragm assembly is mounted on the earphone frame, and a sweep frequency tester applies a sinusoidal excitation from 20Hz to 20kHz, recording the diaphragm's frequency response. The test results reveal a +5dB resonance peak at 2kHz, which can cause high-frequency sounds to be too sharp and affect the listening experience. Analysis suggests that this is due to insufficient rigidity of the folded edge structure at the diaphragm, resulting in excessive localized vibration at specific frequencies. To address this issue, the curvature of the folded edge structure was fine-tuned to increase its edge rigidity. The adhesive was also optimized, using a type with higher damping properties to suppress localized vibration. After these adjustments, a sweep frequency test was repeated. The new frequency response curve shows that the resonance peak at 2kHz has been effectively suppressed, with the deviation reduced to within +2dB, meeting the preset requirements. However, testing also revealed a slight attenuation in the low-frequency range (below 50Hz). Further adjustments were made to the winding angle of the carbon fiber voice coil bobbin to increase vibration efficiency in this low-frequency range. After three iterations of adjustments and testing, the diaphragm assembly's frequency response finally met the ±3dB requirement, achieving the expected acoustic performance. This completed the optimization and resulted in the speaker diaphragm assembly.

[0029] In one embodiment, the high molecular polymer is a mixture of any one or more of polyimide, polyetheretherketone, polyethylene terephthalate, and polycarbonate.

[0030] In one embodiment, the step of molding a high molecular polymer to form a diaphragm substrate with a hem-folded structure includes: Under the conditions of a second mold temperature of 250-300° C. and a pressure of 10-15 MPa, the polymer is molded to obtain an initial hem-folded matrix, wherein the second mold adopts an asymmetric wavy design, the amplitude of the wavy design of the second mold is 0.2-0.5 mm, and the wave pitch is 1.0-1.5 mm; The initial folded edge substrate is placed in an ultrasonic cleaning device for cleaning, using deionized water as the cleaning medium, setting the ultrasonic frequency to 40-60 kHz, and the cleaning time to 5-10 minutes to obtain an initial diaphragm substrate; performing vacuum drying on the initial diaphragm matrix to obtain a dry diaphragm matrix; The folded edge structure of the dry diaphragm substrate is corrected by laser to obtain a folded edge structure diaphragm substrate, wherein the laser wavelength is 532 nm and the pulse width is 10-20 ns.

[0031] In this embodiment, during the molding process of the polymer, the temperature of the second mold is set to 250~300°C. This temperature range allows the polymer to reach an appropriate softening state, facilitating flow and molding. The pressure range is 10~15MPa, allowing the polymer to fully fill the microstructure of the mold and form a precise folded edge shape. The amplitude of the asymmetric wavy mold is 0.2~0.5mm, and the wave pitch is 1.0~1.5mm. This design can give the diaphragm substrate specific geometric properties, so that it has an optimized balance of flexibility and rigidity during vibration. For example, the wavy folded edge structure can increase the elasticity of the diaphragm, thereby improving low-frequency response, while avoiding excessive rigidity causing high-frequency distortion. Deionized water is used as the cleaning medium, the ultrasonic frequency is 40~60kHz, and the cleaning time is 5~10 minutes. Deionized water does not introduce new impurities due to its high purity. Ultrasonic cleaning generates tiny bubbles through high-frequency vibration and instantly explodes, which can effectively remove microscopic contaminants on the surface of the substrate. The initial diaphragm substrate undergoes vacuum drying to remove residual moisture and other volatile substances from the cleaning process. This vacuum drying is performed in a vacuum oven. The temperature and vacuum level must be precisely controlled based on the polymer's characteristics. For example, drying should be performed at a low temperature of 80-100°C for 2-4 hours to prevent high temperatures from affecting the geometry of the folded edge structure. Through vacuum drying, the initial diaphragm substrate's moisture content can be reduced to below 0.1%, ensuring both surface and internal dryness. The folded edge structure of the dried diaphragm substrate undergoes laser trimming to further optimize its geometric accuracy and surface quality, resulting in the final folded edge structure. Laser trimming utilizes a 532nm wavelength laser with a pulse width of 10-20ns. This green laser boasts high precision and low thermal impact, making it suitable for processing fine polymer structures. Laser trimming corrects minor deviations in the folded edge structure, such as edge burrs or non-uniformity in the wavy structure that may occur during the molding process, thereby ensuring that the diaphragm substrate's vibration characteristics meet design requirements. For example, if the amplitude of the hem formed by die pressing slightly exceeds 0.5mm in some areas, laser correction can remove excess material through precise ablation, so that the amplitude is precisely controlled to 0.3mm while maintaining the smoothness of the hem surface. In actual operation, a laser processing system can be used to control the laser beam to scan along the hem path through a computer, with a pulse width set to 15ns. Each correction removes about 1~2μm of material thickness. After multiple scans, the geometric accuracy of the hem structure reaches the tolerance requirement of ±0.01mm.

[0032] In one embodiment, the step of placing the folded edge structure diaphragm substrate in a deposition chamber for cathode arc deposition to obtain a diamond-coated diaphragm includes: The folded edge structure diaphragm substrate is placed in a deposition chamber, the deposition chamber is evacuated to 10-5 Pa, hydrogen is introduced as a protective gas, and the deposition chamber is preheated to 80-100° C. Using a high-purity graphite target as a cathode, starting cathode arc discharge to perform low-speed pre-deposition on the surface of the folded edge structure diaphragm substrate, wherein the DC voltage of the cathode arc discharge is 400 V, the arc current is 40 A, the deposition rate is 0.2-0.3 nm / s, and the deposition time is 5-10 minutes; The main deposition treatment is performed on the surface of the folded edge structure diaphragm substrate, the arc current is adjusted to 50~80A, and a -100V pulse bias is applied, the deposition rate is increased to 0.5~1nm / s, and the deposition is continued for 20~30 minutes. At the same time, hydrogen is introduced into the deposition chamber to obtain a diamond-coated diaphragm.

[0033] In this embodiment, the folded edge structure diaphragm substrate is placed in the deposition cavity, and the cavity is vacuumed to 10 -5 Pa vacuum, hydrogen is introduced as a protective gas, and the chamber is preheated to 80~100°C to create a clean and stable environment for cathodic arc deposition. -5The ultra-high vacuum state of Pa effectively removes residual gases and impurities within the chamber, preventing oxygen and moisture from interfering with the formation of diamond coatings. Hydrogen, as a shielding gas, maintains a low-oxygen environment within the chamber and reacts with carbon atoms during the deposition process, promoting the formation of diamond-like carbon (DLC) or diamond films. Preheating the chamber to a temperature range of 80-100°C helps increase substrate surface activity and enhance the adhesion of the deposited material. Low-speed pre-deposition is performed using a high-purity graphite target as the cathode, initiating cathodic arc discharge. Specific parameters include a DC voltage of 400V, an arc current of 40A, a deposition rate of 0.2-0.3nm / s, and a deposition time of 5-10 minutes. Cathodic arc deposition is a physical vapor deposition (PVD) technique that uses arc discharge to generate plasma on the graphite target surface, releasing carbon atoms that are deposited on the substrate surface, forming a DLC or diamond film. The purpose of the low-speed pre-deposition is to form a uniform initial carbon film on the substrate surface, improving the adhesion and film quality of the subsequent main deposition. The high purity of the graphite target (typically ≥99.99%) ensures the purity of carbon atoms in the deposited film, preventing impurities from affecting the film's hardness and optical properties. A combination of a DC voltage of 400V and an arc current of 40A produces a stable arc discharge, generating an appropriate amount of carbon plasma. A low deposition rate of 0.2-0.3nm / s ensures uniformity and density of the initial film. For example, in a production process, engineers select an 8-minute deposition time and a controlled deposition rate of 0.25nm / s. During the pre-deposition process, an initial carbon film approximately 100-150nm thick forms on the surface of the hem-shaped diaphragm substrate. This thin film not only covers the wavy areas of the hem structure but also reduces stress accumulation due to the low deposition rate, preventing the risk of cracking or delamination. Successful implementation of the low-speed pre-deposition provides a high-quality transition layer for the subsequent main deposition, ensuring the overall performance of the diamond coating. By adjusting the arc current to 50~80A and applying a -100V pulse bias, the deposition rate is increased to 0.5~1nm / s, and the deposition is continued for 20~30 minutes while continuing to introduce hydrogen, and finally a diamond-coated diaphragm is obtained. The increase in arc current in the main deposition stage can enhance the density of the plasma and accelerate the deposition rate of carbon atoms, thereby forming a thicker film layer in a shorter time. The application of a -100V pulse bias guides the carbon ions to be deposited directionaly on the surface of the substrate through the action of the electric field, thereby improving the density and surface smoothness of the film layer and reducing defects in the film. The increase in the deposition rate of 0.5~1nm / s enables the film thickness to reach 500~1800nm ​​within 20~30 minutes, meeting the diaphragm's requirements for hardness and acoustic performance. The continuous introduction of hydrogen can react with the non-sp³ hybrid bonds in the carbon atoms, remove the amorphous carbon component, and thus increase the sp 3 The key ratio is improved to make it closer to the crystal structure of diamond, and a diamond coating is formed on the surface of the folded edge structure diaphragm substrate.

[0034] In one embodiment, the step of placing the diamond-coated diaphragm in a thermal evaporation chamber under a vacuum environment and performing thermal evaporation deposition on the diamond-coated diaphragm to obtain the evaporated diaphragm includes: The diamond-coated diaphragm is placed in a thermal evaporation chamber, the vacuum degree in the thermal evaporation chamber is adjusted to 10-7 Pa, argon is introduced as a protective gas, and the temperature in the thermal evaporation chamber is raised to 200-220°C and kept constant; Using a platinum target as an evaporation source, heating the platinum target to 1800° C. using an electron beam heating device, controlling the deposition rate to 0.2 nm / s, and performing thermal evaporation deposition on the surface of the diamond-coated diaphragm for 15 to 20 minutes to obtain a primary platinum-coated diaphragm; A titanium target was used as an auxiliary evaporation source, and the titanium target was heated to 1600°C by an electron beam heating device. The deposition rate was controlled to be 0.1 nm / s, and a secondary thermal evaporation deposition treatment was performed on the surface of the primary platinum-coated diaphragm. The deposition time was 10 minutes to obtain the evaporated diaphragm.

[0035] In this embodiment, the diamond-coated diaphragm is placed in a thermal evaporation chamber, and the vacuum degree in the chamber is adjusted to 10 -7 Pa, and introduce argon as a protective gas, and raise the temperature in the chamber to 200-220°C and keep it constant, and adjust the vacuum degree to 10 -7The ultra-high vacuum state of Pa significantly reduces the presence of residual gas molecules (such as oxygen and water vapor) within the chamber, preventing these impurities from reacting with the evaporated material during the high-temperature deposition process and affecting the coating quality. Maintaining a constant chamber temperature of 200-220°C enhances the thermal activity of the diaphragm surface, promoting the adhesion of the evaporated material and uniform film formation. A platinum target is used as the evaporation source. A high-energy electron beam heats the target, energizing its surface atoms to evaporate. These atoms then deposit onto the substrate in a vacuum environment, forming a thin film. An electron beam heating device controls the temperature of the platinum target, heating it to 1800°C. This releases platinum atoms from the target in gaseous form, allowing them to enter the chamber and deposit onto the diaphragm surface. A low deposition rate of 0.2 nm / s facilitates the formation of a uniform, dense platinum film, avoiding film defects or stress accumulation caused by excessively rapid deposition. A deposition time of 15-20 minutes ensures that the platinum coating reaches an appropriate thickness (approximately 180-240 nm) to cover the surface of the diamond-coated diaphragm while maintaining its original geometry and acoustic properties. Titanium has a lower melting point (approximately 1668°C) than platinum. Heating to 1600°C ensures stable evaporation of the titanium target while preventing thermal stress on the primary platinum or diamond coatings caused by excessive temperatures. The deposition rate is controlled at 0.1 nm / s, lower than that of platinum deposition. This is primarily to form an extremely thin and uniform titanium film (approximately 60 nm) on the platinum surface, further enhancing the surface hardness and wear resistance of the diaphragm while maintaining its flexibility and acoustic response. The introduction of the titanium film may form a composite coating structure through interfacial interaction with the platinum film, thereby maintaining the diaphragm's conductivity while further enhancing its mechanical properties and environmental adaptability. The continuous flow of argon is also important in the secondary deposition. Its inert protective effect can prevent the titanium atoms from being oxidized during the evaporation and deposition process, ensuring the purity and quality of the titanium film, thereby obtaining the vapor-deposited diaphragm. In one embodiment, the step of selecting a high modulus carbon fiber prepreg and performing a wet winding process on a first mold at a preset angle to obtain a carbon fiber voice coil bobbin includes: Performing a wet winding process on the first mold with the high modulus carbon fiber prepreg at a preset angle, wherein the preset angle is 40-50 degrees and the number of winding layers is 3-6, to obtain a primary winding body; The primary winding body and the first mold are placed in a high-temperature curing furnace for curing treatment, maintained at a temperature of 120-125° C. for 120-150 minutes, and then raised to 180-190° C. and maintained for 200-230 minutes to obtain a cured carbon fiber skeleton; The solidified carbon fiber skeleton is placed in a deposition chamber, and a nano-scale silicon carbide coating is deposited on the surface of the solidified carbon fiber skeleton, wherein the target power is 200-300W and the deposition time is 10-15 minutes to obtain the carbon fiber voice coil skeleton.

[0036] In this embodiment, high-modulus carbon fiber prepreg is wet-wound on a first mold at a preset angle of 40-50°, with 3-6 layers wound to produce a primary wound body. High-modulus carbon fiber prepreg is a composite material composed of high-strength, high-modulus carbon fibers pre-impregnated with a resin (such as epoxy resin). It exhibits excellent mechanical properties, including high tensile strength, rigidity, and low density. Wet-wound prepreg is formed by winding the prepreg at a specific angle around a mold to create the desired shape. The preset angle of 40-50° is chosen based on the complex stresses that voice coil bobbins must withstand in acoustic devices. This angle range optimizes the distribution of mechanical properties in the axial and circumferential directions, ensuring good tensile and torsional resistance during dynamic vibration. The 3-6 layers setting balances bobbin thickness and weight. Too few layers may result in insufficient strength, while too many layers increase mass and affect the voice coil's response speed. The first mold can be designed in a cylindrical or conical shape to accommodate the voice coil's assembly requirements within the speaker. During the wet winding process, the resin in the prepreg remains moist during winding. A tension control device ensures that the fibers adhere closely to the mold surface, preventing defects such as bubbles and ruffles, thereby forming a uniformly structured primary winding. The primary winding, along with the first mold, is then placed in a high-temperature curing oven for curing. The temperature is initially maintained at 120-125°C for 120-150 minutes, then raised to 180-190°C and maintained for 200-230 minutes, resulting in a cured carbon fiber skeleton. High-temperature curing heat-treats the resin in the prepreg, cross-linking it to form a robust matrix structure while securely locking the carbon fibers in place. The initial low-temperature curing at 120-125°C allows the resin to cure slowly, releasing any residual internal stresses from the winding process while also preventing uneven resin flow and bubble formation caused by rapid heating. Maintaining the temperature for 120-150 minutes ensures that the resin fully penetrates the interstices between the fibers, forming a uniform matrix structure. The temperature is then raised to 180-190°C and held for 200-230 minutes to complete the deep cross-linking reaction of the resin and further enhance the mechanical strength and thermal stability of the cured carbon fiber skeleton. The temperature control strategy during this stage not only optimizes the degree of resin cure but also prevents potential damage to the carbon fiber properties caused by high temperatures. During the curing process, the first mold continues to shape the primary winding, ensuring that it does not deform at high temperatures. The mold's thermal conductivity also helps to evenly transfer heat and promote a uniform curing reaction. After curing, the primary winding is transformed into a cured carbon fiber skeleton with high strength and rigidity. The cured carbon fiber skeleton is placed in a deposition chamber, where a nanoscale silicon carbide coating is deposited on its surface. The target power is 200-300W, and the deposition time is 10-15 minutes, resulting in a carbon fiber voice coil skeleton. Silicon carbide is a highly hard, wear-resistant, and high-temperature resistant ceramic material. Its nanoscale coating significantly improves the surface properties of the carbon fiber skeleton, extending the life of the voice coil.The deposition process can use physical vapor deposition (PVD) techniques, such as magnetron sputtering or ion beam deposition, in which high-energy particles bombard a silicon carbide target, causing its surface atoms to sputter and deposit onto the surface of the carbon fiber skeleton. Setting the target power to 200-300W can control the sputtering rate, ensuring that the silicon carbide atoms are deposited on the substrate surface with appropriate energy, forming a uniform and dense nanoscale coating. The deposition time of 10-15 minutes controls the coating thickness, which can range from tens to hundreds of nanometers, significantly improving the surface hardness and wear resistance without significantly increasing the mass of the skeleton or changing its geometry. The introduction of the silicon carbide coating not only improves the skeleton's wear resistance, but also enhances its stability in high-temperature or high-frequency vibration environments, thereby optimizing the dynamic performance of the voice coil skeleton in the speaker.

[0037] In one embodiment, the step of bonding the evaporated diaphragm and the carbon fiber voice coil bobbin with high-rigidity glue to obtain a diaphragm assembly includes: Placing the evaporated diaphragm and the carbon fiber voice coil frame in an ultraviolet ozone cleaning device to clean the surfaces of the evaporated diaphragm and the carbon fiber voice coil frame; The epoxy resin and the curing agent are mixed and stirred in a mass ratio of 10 to 9:1, and silica particles are added during the mixing process to obtain a high-rigidity glue; Applying the high-rigidity glue in a dispensing amount of 0.015-0.025 g to the bonding area of ​​the cleaned evaporated diaphragm and the carbon fiber voice coil frame, and then performing an alignment bonding process to obtain a preliminary bonding assembly; The preliminary bonding assembly is placed in a constant temperature curing oven and subjected to low temperature curing treatment at a temperature of 25 to 30°C for 1.5 to 2.5 hours to obtain the diaphragm assembly.

[0038] In this embodiment, the vapor-deposited diaphragm and carbon fiber voice coil bobbin are placed in a UV-ozone cleaning device to clean their surfaces. UV-ozone cleaning uses ultraviolet light to excite oxygen in the air to generate ozone, which is then decomposed into reactive oxygen atoms. These reactive oxygen atoms effectively oxidize and remove organic contaminants from the surface, while also introducing hydroxyl groups or other reactive groups onto the material surface, thereby improving surface wettability and chemical activity. This surface modification not only enhances the bond between the material and the adhesive but also ensures the uniformity and stability of the bonding interface. The cleaning process is performed at room temperature and lasts from several minutes to over ten minutes, depending on the degree of surface contamination and the equipment power, to ensure optimal bonding. Epoxy resin and curing agent are mixed and stirred in a mass ratio of 10 to 9:1. Silica particles are added during the mixing process to produce a high-rigidity adhesive. Epoxy resin is a commonly used high-performance adhesive with excellent bond strength, chemical resistance, and mechanical stability. Curing agents (such as amines or anhydrides) react with epoxy groups to form a three-dimensional cross-linked network, imparting high hardness and rigidity to the cured adhesive. Silica, an inorganic filler, exhibits high hardness and a low thermal expansion coefficient. Its micron- or nanometer-sized particles significantly enhance the adhesive's mechanical properties and shear resistance. The addition of silica slightly increases the adhesive's viscosity, but it must still maintain adequate fluidity for easy dispensing. Apply a high-rigidity adhesive in a dispensing amount of 0.015-0.025g to the bonding area of ​​the cleaned vapor-deposited diaphragm and carbon fiber voice coil former, followed by alignment and bonding to create a preliminary bonded assembly. Dispensing can be performed using dispensing equipment, such as pneumatic or electric dispensers, by controlling the needle size and pressure to achieve uniform application of a small amount of adhesive. The bonding area should be selected based on the structural design of the diaphragm and voice coil former. This can be the junction between the diaphragm edge and the voice coil former to ensure efficient vibration transmission and structural stability. Alignment bonding requires precise spatial alignment of the vapor-deposited diaphragm and carbon fiber voice coil former. This can be achieved using a fixture or a visual alignment system to ensure geometric accuracy of the bonded assembly. Appropriate pressure should be applied during the bonding process to ensure even distribution of the glue across the interface, while avoiding excessive pressure that could cause glue overflow or diaphragm deformation. The pre-bonded assembly is placed in a constant-temperature curing oven for a low-temperature curing process at 25-30°C for 1.5-2.5 hours to obtain the diaphragm assembly. Low-temperature curing allows the epoxy resin and curing agent to react slowly, forming a uniform cross-linked network and avoiding thermal stress or material deformation that can occur with high-temperature curing. The constant-temperature curing oven provides a stable temperature environment, preventing temperature fluctuations from interfering with the curing reaction. Furthermore, low-temperature curing eliminates the risk of damaging the composite material of the vapor-deposited diaphragm and the carbon fiber voice coil former, ensuring the acoustic and mechanical properties of the assembly.After curing, the epoxy resin in the high-rigidity glue forms a strong three-dimensional cross-linked structure, and the silica particles further enhance the hardness and fatigue resistance of the glue layer, giving the diaphragm assembly excellent vibration transmission efficiency and long-term reliability.

[0039] In one embodiment, the step of performing a frequency sweep test on the diaphragm assembly and adjusting the vibration characteristics of the diaphragm assembly according to the test results until the preset performance requirements are met to obtain a loudspeaker diaphragm assembly includes: Applying a sinusoidal wave excitation signal to the diaphragm assembly within a preset frequency range, measuring the amplitude, phase, and frequency response characteristics of the diaphragm assembly, and obtaining preliminary vibration characteristic data; Determining whether the preliminary vibration characteristic data meets preset performance requirements; If not, based on the difference between the preliminary vibration characteristic data and the preset performance requirements, a polymer damping material is coated on the edge area of ​​the diaphragm assembly to adjust the boundary vibration characteristics of the diaphragm assembly until the preliminary vibration characteristic data meets the preset performance requirements, thereby obtaining a speaker diaphragm assembly.

[0040] In this embodiment, the initial frequency sweep test applies a sinusoidal excitation signal to comprehensively acquire preliminary vibration characteristic data of the diaphragm assembly. Specifically, within a preset frequency range, typically covering the operating frequency range of a loudspeaker (e.g., 20 Hz to 20 kHz), a sinusoidal signal is applied to the diaphragm assembly using high-precision audio analysis equipment. This signal is applied to the diaphragm at progressively increasing frequencies. The equipment records the diaphragm's amplitude, phase, and frequency response characteristics at each frequency in real time, generating a detailed set of preliminary vibration characteristic data. After obtaining this preliminary vibration characteristic data, the diaphragm's vibration behavior is further analyzed through finite element simulation. Finite element simulation is a computationally based analysis method that builds a three-dimensional digital model of the diaphragm assembly and inputs preliminary vibration characteristic data into the model to simulate the vibration modes of the diaphragm under excitation at different frequencies. This process can be performed using a high-performance computing platform capable of handling complex numerical calculations. The simulation model combines the diaphragm's material properties (such as Young's modulus, density, Poisson's ratio), as well as geometric parameters (such as thickness, shape, and edge constraints) to calculate the diaphragm's modal shape, nodal line locations, and resonance peak characteristics at each frequency. By analyzing the vibration mode distribution, it's possible to identify whether the diaphragm exhibits excessive amplitude or unwanted resonance at specific frequencies. For example, if simulation results show excessive amplitude in the center of the diaphragm at a certain frequency, adjustments to the mass distribution or stiffness in that area may be necessary to suppress the abnormal vibration. Based on the vibration mode distribution analysis, the diaphragm assembly undergoes localized mass adjustment to optimize its vibration characteristics. This process involves adding or removing small amounts of high-density material, such as metal films or polymer composites, to specific areas of the diaphragm. This adjustment typically utilizes precision laser etching or micro-material deposition techniques to ensure precise addition or removal of material. For example, if simulations reveal that the vibration mode in a specific area results in an excessively high resonance peak, localized mass can be added by depositing small amounts of high-density material in that area, thereby modifying the vibration characteristics. Conversely, if the amplitude in a specific area is insufficient, laser etching can be used to remove material to reduce the mass. The goal of these adjustments is to balance the diaphragm's vibration modes and suppress unwanted resonance peaks, while maintaining the diaphragm's overall stiffness and lightweight characteristics to ensure optimal acoustic performance and mechanical durability in the loudspeaker. This process requires repeated verification of the adjustment effect to ensure that each fine-tuning can gradually approach the preset performance requirements. After completing the mass distribution adjustment, a second frequency sweep test is performed on the optimized diaphragm assembly to evaluate the adjustment effect and obtain optimized vibration characteristic data. The conditions of the second frequency sweep test are consistent with the initial test. The same frequency range and sinusoidal wave excitation signal are used to measure the amplitude, phase and frequency response characteristics of the diaphragm through high-precision sensors and spectrum analyzers. Compared with the initial test, the focus of the second test is to verify whether the mass distribution adjustment has effectively improved the vibration behavior of the diaphragm, such as whether abnormal resonance has been successfully suppressed or the frequency response curve has been optimized.The test results generate a set of optimized vibration characteristic data. Comparing these data with the initial data provides a visual representation of the adjustment results. If the data indicates that the diaphragm's vibration characteristics have significantly improved but still do not fully meet the preset requirements, further optimization is required. Based on the analysis of the optimized vibration characteristic data, the diaphragm assembly undergoes boundary damping treatment to further adjust its vibration characteristics. This process focuses on the diaphragm's edge areas, modifying the diaphragm's boundary vibration characteristics by coating it with a polymer damping material or bonding it with a flexible damping layer. Polymer damping materials typically have high internal friction, effectively absorbing vibration energy and reducing vibration interference caused by boundary reflections. Automated coating equipment is used to ensure uniform thickness and distribution of the damping material, ensuring good adhesion. For example, by controlling the thickness of the damping layer (between 0.1 mm and 0.5 mm) and the extent of the coating area, the diaphragm's damping coefficient can be precisely adjusted to optimize its acoustic stability. The goal of boundary damping treatment is to reduce vibration reflections at the diaphragm's edges, improving the smoothness of the frequency response, while also preventing excessive damping from affecting the diaphragm's sensitivity. This process combines optimized vibration characteristic data with multiple tests to ensure that the damping effect matches the preset performance requirements. The diaphragm assembly, after damping optimization, undergoes final performance verification testing to confirm that it meets the speaker's performance requirements. This testing is conducted in an acoustic test chamber that simulates actual usage conditions. The diaphragm assembly is assembled into the speaker frame and subjected to multi-band sweep tests to measure sound pressure level, distortion, and frequency response characteristics. The testing equipment typically includes a multi-channel audio analysis system capable of comprehensively evaluating the diaphragm's acoustic performance and mechanical stability. For example, sound pressure level testing verifies the diaphragm's output capacity at different frequencies, distortion testing assesses its nonlinear distortion levels, and frequency response testing confirms that its overall acoustic performance is smooth and meets design requirements. If the test results indicate that the diaphragm assembly's performance meets the preset standards, such as stable sound pressure level, distortion below 1%, and a smooth frequency response curve, it can be confirmed as the final speaker diaphragm assembly. If deficiencies remain, the previous steps must be repeated to further adjust the specific issues until the requirements are met.

[0041] In another embodiment, the calculation expression of the above embodiment is: ;in, To optimize the vibration characteristic index, it indicates the comprehensive vibration characteristic score of the diaphragm assembly after optimization. The lower the value, the closer the diaphragm performance is to the preset requirements. Integral for the frequency range, for the frequency range [ , ] to integrate over the operating frequency of the loudspeaker (e.g., 20 Hz to 20 kHz); is the amplitude response, which indicates the amplitude response of the diaphragm at frequency f, reflecting the vibration intensity of the diaphragm; Φ(f) is the phase response, which indicates the phase response of the diaphragm at frequency f, indicating the phase difference between the vibration signal and the excitation signal; R(f) is the actual frequency response, which indicates the actual frequency response of the diaphragm at frequency ff; is the reference frequency response, which represents the preset ideal frequency response curve, i.e. the target acoustic performance; is the frequency response deviation, which represents the absolute deviation between the actual frequency response and the reference response; is the mass distribution adjustment factor, which represents the degree of adjustment of the local mass distribution of the diaphragm at frequency f, achieved by adding or removing material; is the boundary damping factor, which represents the damping characteristics of the diaphragm edge area at frequency f, and is adjusted by coating polymer damping material; , and are weight coefficients, which are the weight coefficients of amplitude, phase and frequency response deviation, respectively, and are used to balance the contributions of the three in the optimization; and are the damping influence coefficients, which are the exponential influence coefficients of mass adjustment and boundary damping on vibration characteristics; is an exponential decay term, which represents the combined inhibitory effect of mass adjustment and boundary damping on vibration characteristics; this calculation expression comprehensively considers the amplitude, phase and frequency response deviation of the diaphragm in the entire frequency range in the form of an integral, and balances the contributions of the three through a weight coefficient. The exponential term introduces the nonlinear effects of mass adjustment and boundary damping to simulate the complex dynamic behavior in the actual optimization process. The formula output serves as the optimization target to guide the iterative adjustment of the diaphragm until the preset performance requirements (such as distortion rate <1%, smooth frequency response) are met. It is worth noting that this formula expression is a further optimization based on the original implementation example, and does not affect the original technical effects and core of this application.

[0042] As described above, the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for manufacturing a loudspeaker diaphragm, characterized in that: include: Molding a high molecular polymer to form a folded edge structure diaphragm substrate, placing the folded edge structure diaphragm substrate in a deposition chamber for cathode arc deposition to obtain a diamond-coated diaphragm; In a vacuum environment, the diamond-coated diaphragm is placed in a thermal evaporation chamber, and a thermal evaporation deposition process is performed on the diamond-coated diaphragm to obtain a vapor-deposited diaphragm; High modulus carbon fiber prepreg is selected and wet-wound at a preset angle on the first mold to obtain a carbon fiber voice coil bobbin; Bonding the evaporated diaphragm and the carbon fiber voice coil frame with high-rigidity glue to obtain a diaphragm assembly; A frequency sweep test is performed on the diaphragm assembly, and the vibration characteristics of the diaphragm assembly are adjusted according to the test results until the preset performance requirements are met, thereby obtaining a loudspeaker diaphragm assembly.

2. The method for manufacturing a loudspeaker diaphragm according to claim 1, wherein: The high molecular polymer is a mixture of any one or more of polyimide, polyetheretherketone, polyethylene terephthalate, and polycarbonate.

3. The method for manufacturing a loudspeaker diaphragm according to claim 1, wherein: The step of molding the high molecular polymer to form a diaphragm matrix with a folded edge structure includes: Under the conditions of a second mold temperature of 250-300° C. and a pressure of 10-15 MPa, the polymer is molded to obtain an initial hem-folded matrix, wherein the second mold adopts an asymmetric wavy design, the amplitude of the wavy design of the second mold is 0.2-0.5 mm, and the wave pitch is 1.0-1.5 mm; The initial folded edge substrate is placed in an ultrasonic cleaning device for cleaning, using deionized water as the cleaning medium, setting the ultrasonic frequency to 40-60 kHz, and the cleaning time to 5-10 minutes to obtain an initial diaphragm substrate; performing vacuum drying on the initial diaphragm matrix to obtain a dry diaphragm matrix; The folded edge structure of the dry diaphragm substrate is corrected by laser to obtain a folded edge structure diaphragm substrate, wherein the laser wavelength is 532 nm and the pulse width is 10-20 ns.

4. The method for manufacturing a loudspeaker diaphragm according to claim 1, wherein: The step of placing the folded edge structure diaphragm substrate in a deposition chamber for cathode arc deposition to obtain a diamond-coated diaphragm comprises: The folded edge structure diaphragm substrate is placed in a deposition chamber, the deposition chamber is evacuated to 10-5 Pa, hydrogen is introduced as a protective gas, and the deposition chamber is preheated to 80-100° C. Using a high-purity graphite target as a cathode, starting cathode arc discharge to perform low-speed pre-deposition on the surface of the folded edge structure diaphragm substrate, wherein the DC voltage of the cathode arc discharge is 400 V, the arc current is 40 A, the deposition rate is 0.2-0.3 nm / s, and the deposition time is 5-10 minutes; The main deposition treatment is performed on the surface of the folded edge structure diaphragm substrate, the arc current is adjusted to 50~80A, and a -100V pulse bias is applied, the deposition rate is increased to 0.5~1nm / s, and the deposition is continued for 20~30 minutes. At the same time, hydrogen is introduced into the deposition chamber to obtain a diamond-coated diaphragm.

5. The method for manufacturing a loudspeaker diaphragm according to claim 1, wherein: The step of placing the diamond-coated diaphragm in a thermal evaporation chamber under a vacuum environment and performing thermal evaporation deposition on the diamond-coated diaphragm to obtain the evaporated diaphragm comprises: The diamond-coated diaphragm is placed in a thermal evaporation chamber, the vacuum degree in the thermal evaporation chamber is adjusted to 10-7 Pa, argon is introduced as a protective gas, and the temperature in the thermal evaporation chamber is raised to 200-220°C and kept constant; Using a platinum target as an evaporation source, heating the platinum target to 1800° C. using an electron beam heating device, controlling the deposition rate to 0.2 nm / s, and performing thermal evaporation deposition on the surface of the diamond-coated diaphragm for 15 to 20 minutes to obtain a primary platinum-coated diaphragm; A titanium target was used as an auxiliary evaporation source, and the titanium target was heated to 1600°C by an electron beam heating device. The deposition rate was controlled to be 0.1 nm / s, and a secondary thermal evaporation deposition treatment was performed on the surface of the primary platinum-coated diaphragm. The deposition time was 10 minutes to obtain the evaporated diaphragm.

6. The method for manufacturing a loudspeaker diaphragm according to claim 1, wherein: The step of selecting a high modulus carbon fiber prepreg and performing a wet winding process on a first mold at a preset angle to obtain a carbon fiber voice coil bobbin includes: Performing a wet winding process on the first mold with the high modulus carbon fiber prepreg at a preset angle, wherein the preset angle is 40-50 degrees and the number of winding layers is 3-6, to obtain a primary winding body; The primary winding body and the first mold are placed in a high-temperature curing furnace for curing treatment, maintained at a temperature of 120-125° C. for 120-150 minutes, and then raised to 180-190° C. and maintained for 200-230 minutes to obtain a cured carbon fiber skeleton; The solidified carbon fiber skeleton is placed in a deposition chamber, and a nano-scale silicon carbide coating is deposited on the surface of the solidified carbon fiber skeleton, wherein the target power is 200-300W and the deposition time is 10-15 minutes to obtain the carbon fiber voice coil skeleton.

7. The method for manufacturing a loudspeaker diaphragm according to claim 1, wherein: The step of bonding the evaporated diaphragm and the carbon fiber voice coil frame with high-rigidity glue to obtain a diaphragm assembly includes: Placing the evaporated diaphragm and the carbon fiber voice coil frame in an ultraviolet ozone cleaning device to clean the surfaces of the evaporated diaphragm and the carbon fiber voice coil frame; The epoxy resin and the curing agent are mixed and stirred in a mass ratio of 10 to 9:1, and silica particles are added during the mixing process to obtain a high-rigidity glue; Applying the high-rigidity glue in a dispensing amount of 0.015-0.025 g to the bonding area of ​​the cleaned evaporated diaphragm and the carbon fiber voice coil frame, and then performing an alignment bonding process to obtain a preliminary bonding assembly; The preliminary bonding assembly is placed in a constant temperature curing oven and subjected to low temperature curing treatment at a temperature of 25 to 30°C for 1.5 to 2.5 hours to obtain the diaphragm assembly.

8. The method for manufacturing a loudspeaker diaphragm according to claim 1, wherein: The step of performing a frequency sweep test on the diaphragm assembly and adjusting the vibration characteristics of the diaphragm assembly according to the test results until the preset performance requirements are met to obtain the loudspeaker diaphragm assembly includes: Applying a sinusoidal wave excitation signal to the diaphragm assembly within a preset frequency range, measuring the amplitude, phase, and frequency response characteristics of the diaphragm assembly, and obtaining preliminary vibration characteristic data; Determining whether the preliminary vibration characteristic data meets preset performance requirements; If not, based on the difference between the preliminary vibration characteristic data and the preset performance requirements, a polymer damping material is coated on the edge area of ​​the diaphragm assembly to adjust the boundary vibration characteristics of the diaphragm assembly until the preliminary vibration characteristic data meets the preset performance requirements, thereby obtaining a speaker diaphragm assembly.

9. A loudspeaker diaphragm, characterized in that: The loudspeaker diaphragm is manufactured by the manufacturing method according to any one of claims 1 to 8.

10. A speaker, characterized in that: The loudspeaker diaphragm comprises the loudspeaker diaphragm according to claim 9, and a magnetic circuit system and a voice coil assembly connected to the loudspeaker diaphragm.

Citation Information

Patent Citations

  • Speaker diaphragm and method of making the same

    CA1087105A

  • Vibration membrane and loudspeaker applying same

    CN101990148A

  • Loudspeaker diaphragm and manufacturing method thereof, loudspeaker and electronic equipment

    CN117835125A

  • The diaphragm coated by polymer metalization at lowtemperature

    KR1020020079634A